WOMAN, DRUG CONSUMPTION AND VIOLENCE: COMPLEXITY OF A CURENT PHENOMENON - Musayón Oblitas, Yesenia; Vaiz B, Rosa; Loncharich V, Natalie; Leal D., Helena (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Relationship between woman, drug consumption and violence is a phenomenon which could be visualized clearly in the world. Objective: Analyze relation of this triad from the complexity and interrelation between determinants, risk factors and conditionants about violence and drug consumption of Latin America and discuss any intervention strategies. Methodology: We did a documental revision of research articles in data base from internet such as LIPECS, LILACS, BIREME, SciELO y PUBMED, and institutional reports. We selected ten articles according to inclusion criteria: research articles publicized in indexed journals from 2000 year which includes subject of drug consumption, violence and Peruvian woman. We analyzed titles, abstracts and full articles where we obtained this information. Results: Drug consumption, violence and woman are being little explored in Peru as a phenomenon related strongly, however there are studies which analyze these topics but in a isolated way. Drug consumption is not related just to aggressor is also related to woman attacked. Kind of violence more frequent is verbal; followed physical violence, and sexual violence. In this way, when more women are being affected for this problem, it is important toestablish strategies of intervention that involve at a woman, family and community, to secure a healthy environment for the affected women, their sons, their family and the society, and to be the north for the public politics.